The Vertex Algebra M(1)⁺ and Certain Affine Vertex Algebras of Level −1 - Adamović, D.; Perše, O. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
We give a coset realization of the vertex operator algebra M(1)⁺ with central charge ℓ.